Ghost [videorecording (DVD)] - Zucker, Jerry; Swayze, Patrick; Moore, Demi; Goldberg, Whoopi, 1955- (Distributed by Warner Home Video, 2013)
When a young man is murdered, he uses a medium to contact his living girlfriend in an effort to discover his killer, get revenge, and to say goodbye.